VICE CHANCELLOR’S SPEECH - Odhiambo, Prof. Romanus (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Ladies and gentlemen, It is my utmost pleasure and honor to welcome you all to the beautiful city of Meru, Kenya, as we gather here today for the Third International Conference of Meru University of Science and Technology (MUSTIC 2024). Under the theme "Science in the Service of Climate Action," this conference provides a crucial platform for intellectual exchange, collaboration, and exploration of innovative ideas that will shape our future. I extend my warmest welcome to our distinguished guests and delegates from around the world. Your presence here today reflects the shared commitment to forging a brighter future for all. Over the course of this conference, we will delve into significant sub-themes that capture the breadth and depth of the challenges we face. From agriculture, food security, safety, and biosecurity to business, economy, and society, we will explore the intricate interplay between human well-being and environmental sustainability. Climate change, with its pressing demands for adaptation, mitigation, and resilience, will take center stage as we seek innovative solutions for a sustainable planet. At Meru University of Science and Technology, we are proud to demonstrate our commitment to combating climate change through active participation in key initiatives. Currently, our students are taking part in the two-week long Nairobi Summer School at Chuka University, organized by the Pan African Climate Justice Alliance (PACJA). This involvement not only enriches their knowledge and skills in climate action but also underscores our dedication to fostering a generation of leaders and innovators who are equipped to tackle the pressing environmental challenges of our time. Our Sanitation Research Institute is a beacon of innovation, converting waste into usable products and contributing to a circular economy. Moreover, our commitment to environmental stewardship is evident in our University’s forest cover, which stands at 14%, significantly above the national average of 10%. These initiatives reflect our dedication to creating a sustainable future through science and technology. To our dear partners, National Research Fund (NRF), Pan African Climate Justice Alliance (PACJA), Cooperative Bank, Kenya Commercial Bank, Three Steers Hotel, Alba Hotel, Institution of Engineers of Kenya (IEK) and African Journal of Science and Social Sciences (AJSTSS), we could not have done this without you. I take this opportunity on behalf of the MUST family to say Thank You. We offer our deepest gratitude for the immense support accorded to us. Your contribution is the backing we require to maintain a firm foundation, anchoring our researchers and innovators as they come up with the solutions we need. Thank you for investing in a better tomorrow and believing in our vision to be a center of Excellence in Research and Innovation. Be rest assured that your contribution has been put to good use. MUSTIC is bigger than all of us and we want to ensure that it serves the world even after us. That is the impact we are striving for. This is also the right time to remind members of the Meru University community of the importance of research in the University. Given the fourth industrial revolution, which is technology-based, research has become easier and more accessible. It is now easier to connect to researchers from all over the world with the increasing presence of all nations on the world wide web, making the world a global village. There are now more efforts towards making research findings easily accessible through open access platforms. This is a great time to be alive as knowledge of all types in all disciplines is available at the click of a button on your computer. I would like to, therefore, urge us to embrace the research agenda. We must give our students the best guidance so that they become great researchers. We can take a leaf from the global trend where members of the academia enhance the capabilities of their learners through leading by example. Intellect should be seen in everything that we do, including how we guide our students in the usual courses and in research. Moreover, I am pleased to share that this conference is not only an intellectual endeavor but also an opportunity for edu-tourism. Meru University of Science and Technology, nestled in the picturesque landscapes of Meru, offers a unique blend of academic excellence and natural beauty. We encourage all participants to explore the wonders of our region, immerse themselves in the rich cultural heritage, and forge new connections that will endure beyond this conference. In conclusion, I extend my deepest gratitude to all the organizers, sponsors, and partners who have worked tirelessly to make this event a reality. Your unwavering commitment to research, innovation, and sustainable development is an inspiration to us all. May this conference be a catalyst for transformative ideas, fruitful collaborations, and lasting impact as we seek solutions to the climate agenda. Together, let us embark on this journey of exploration, innovation, and progress in the post-COVID era. Thank you, and I wish you all a successful and enriching conference ahead. God bless you all. Prof. Romanus Odhiambo, Ph.D. Vice Chancellor Meru University of Science and Technology